Kampanye Dalam Jaringan (Daring) Pemilihan Perbekel Serentak di Kabupaten Badung Tahun 2022 Studi Kasus di Desa Dalung, Kecamatan Kuta Utara, Kabupaten Badung: Digitalisasi Kampanye Pemilihan Perbekel di Desa Dalung Tahun 2022 - Ni Luh Ernawati; I Nyoman Yoga Segara; I Gede Sutarya (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2024)
The online campaign for the election of the Perbekel of Dalung in the 2022 Election of the Simultaneous Village Head of the Badung Regency is a campaign activity carried out by the candidate for the Mayor of the Village through social media using the internet or social media networks. Campaigns can choose social media to be used such as Facebook, Instagram, YouTube, WhatsApp etc. The stages of the online campaign for selecting workshop workers are regulated in Badung Regent Regulation Number 78 of 2021 concerning Guidelines for the Selection and Dismissal of Worker Selection, which later technically the stages are issued in the Decree of the Badung Regent Number 104/0419/HK/2021 concerning Determining the Implementation of Simultaneous Worker Elections in Badung Regency Year 2022. This study used qualitative research methods. The online campaign found obstacles including not having a budget listed for the preparation and implementation of the online campaign, the time for carrying out the online campaign was too short, Prospective Worker Candidates were passive in using social media, Voters were not interested in finding information about the Worker Election and the candidate Worker Candidates, Voters did not receive socialization enough about the introduction of the candidates, voters are lazy to open, read and watch campaign messages via the WhatsApp group and the duration of the video that is too long also makes voters lazy to watch, let alone packed with standard procedures, determined in detail by the committee based on applicable regulations. The online campaign in Dalung Village also had several impacts, namely: security in an atmosphere where the online campaign in Dalung Village was safe and controlled, the lack of public enthusiasm was seen from the total participation in the voting which was only 63.3 percent and the online campaign became ineffective for candidates if they did not supported by the activeness of the candidates to socialize previously in the community and passively socializing themselves regularly and periodically on their social media accounts.